Very long-term data on patients with severe eosinophilic asthma treated with mepolizumab: a case series - Carlo Lombardi; Francesco Menzella; Alvise Berti (BioExcel Publishing Ltd, 2024)
Background: Patients with severe asthma are often dependent on oral corticosteroids (OCS) and have frequent exacerbations. This article aims to report very long-term data of patients with severe eosinophilic asthma assessing asthma control, lung function, inhaled corticosteroid (ICS) dose reduction, and clinical and biological parameters of patients treated with mepolizumab. Methods: Four cases of adult patients with severe eosinophilic asthma who were treated for 60 months or more with mepolizumab 100 mg/4 weeks, leading to the stable discontinuation of OCS, are presented. ICS dose, OCS dose and withdrawal date, lung function, eosinophil count, fractional exhaled nitric oxide, and asthma control test were recorded as well as exacerbations in the 12 months before commencing mepolizumab and in the 12 months before the last follow-up visit. Results: Three of the patients were men, median age was 52.5 years (range 79-53), median length of asthma before mepolizumab start was 67.5 months (range 24-240), three had chronic rhinosinusitis without nasal polyposis and two were atopic. All had eosinophil counts >300 cells/μL at baseline. The median follow-up was 73.5 months (range 71-74), and OCS withdrawal from baseline occurred after a median of 13 months of mepolizumab treatment (range 12-39). A substantial reduction of ICS treatment was registered as well as improvement in asthma control test, fractional exhaled nitric oxide and functional parameters, and a significant reduction of exacerbations in the last 12 months before last visit was observed as compared to the 12 months before baseline (from a median of 4 (range 3-6) to 0; p=0.0286). Conclusions: Mepolizumab could be a 'disease-modifying' agent, with high tolerability and a good efficacy profile in the long term.